The effect of the general budget appendices on tax certainty with in the scops of direct taxes - Sabah, Israa; Hadi, Ali (Journal of Legal Sciences, 2022)
The tax certainty base is one of the rules based on the proven tax system so that it must be taken to consider when the tax texts are being confused the absence of causes the effects of astate, The end sought by tax certainty rule is to make the tax law fixed clear, precise, accessible and recognizable.Throught that the aim of the legislation isaccomplished and the taxpayers guarantee about their right and the do the obligation imposed on them.All this is achieved by avoiding continuous amendments to tax laws and attention to legal formulation, so that tax laws are clear free from mystery, confusion and understandable for all people and easily implemetable.